Examining the Components of Pedagogical Expertise Through an Axiological Framework, Using Preschool Education as an Illustrative Example - Mirzakhamdam, Turgunov Mirjalol (Jurnal Pendidikan Non formal, 2024)
This abstract explores the theoretical and methodological foundations of preparing students for teaching roles, employing an axiological framework as a guiding paradigm. The study investigates the development of educational competencies in students through the lens of axiology, emphasizing the values and beliefs that shape effective teaching practices. Axiology, as a branch of philosophy concerned with values and ethics, offers a comprehensive framework for understanding the complex interplay between educators' values, instructional methods, and student learning outcomes. The analysis delves into key components of pedagogical expertise, elucidating how teachers' values and beliefs influence their instructional approaches and interactions with students. By examining the underlying principles of axiology, the study highlights the significance of fostering a value-driven approach to education, where educators prioritize the holistic development of students' intellectual, emotional, and ethical capacities. Furthermore, the study explores practical implications for incorporating axiological principles into teacher training programs and curriculum design. It underscores the importance of cultivating reflective and ethically-minded educators who are capable of promoting inclusive learning environments and fostering students' critical thinking skills. Through case studies and illustrative examples drawn from preschool education, the essay demonstrates how an axiological approach can enhance teaching effectiveness and contribute to the overall quality of education. Overall, this research offers valuable insights into the transformative potential of axiological pedagogy in preparing future educators for the challenges of contemporary teaching practice.